UNCLOS Definition of Piracy: Is it still Relevant for Modern Piracy? - Nilasari Nilasari; Lorna Steele (Jurnal Mulawarman Law Review, 2022)
Nowadays, piracy as one of crimes at sea has formed in different ways compared to the historical counterparts. On the past, the act of piracy consisted of first approaching the ship, then fighting it, and finally seizing it before escaping in another vessel. Meanwhile, in recent times, more sophisticated kinds of piracy are launching their assaults with the help of cutting-edge technology. However, due to UNCLOS's restricted definition of piracy, it is challenging to combat such modern forms. According to experts, one of the greatest barriers to tackling piracy is its restricted and vague definition. This research aims to analyse the applicability of the UNCLOS definition of maritime piracy considering its new developments. This research method consists of doctrinal and library-based research. The previous and recent cases are contrasted to investigate definitional issues. The study revealed that UNCLOS's ambiguous and unclear definition of piracy has caused problems. Regarding contemporary piracy, the UCLOS approach is insufficient to combat well-organized pirate attacks in the modern world.